Bones of the lost - Reichs, Kathy (London : William Heinemann, 2013)
The latest from Kathy Reichs finds Tempe Brennan investigating the connections between a long-dead business man, the smuggling of mummified dogs from Peru, and the death of a teenage girl killed in a hit and run. When she discovers a human trafficking enterprise at the center of it all, the scope of the case extends from South America to Afghanistan. And Tempe's soon-to-be ex might have connections that run to the very heart of the trafficking ring.
Keywords: Women forensic anthropologists -- Fiction; Detective and mystery fiction